2016
DOI: 10.4049/jimmunol.1601040
|View full text |Cite
|
Sign up to set email alerts
|

Local Microenvironment Controls the Compartmentalization of NK Cell Responses during Systemic Inflammation in Mice

Abstract: Systemic inflammatory response syndrome is a whole-body reaction to a triggering insult that often results in life-threatening illness. Contributing to the development of this inflammatory cascade are numerous cellular partners, among which NK cells were shown to play a key role. Accumulating evidence points to organ-specific properties of systemic inflammation and NK cells. However, little is known about compartment-specific activation of NK cells during systemic inflammatory response syndrome or the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…found that, in the setting of sepsis, it is the local microenvironment that mediated the functional adaptation of tissue‐resident NK cells. In this study, tissue‐resident NK cells displayed organ‐specific thresholds of maximum activation and effector functions in lung, spleen, peritoneum, bone marrow and blood . In another study, Victorino et al .…”
Section: Nk Cells: Friend or Foe During Sepsis?supporting
confidence: 55%
See 1 more Smart Citation
“…found that, in the setting of sepsis, it is the local microenvironment that mediated the functional adaptation of tissue‐resident NK cells. In this study, tissue‐resident NK cells displayed organ‐specific thresholds of maximum activation and effector functions in lung, spleen, peritoneum, bone marrow and blood . In another study, Victorino et al .…”
Section: Nk Cells: Friend or Foe During Sepsis?supporting
confidence: 55%
“…In this study, tissue-resident NK cells displayed organ-specific thresholds of maximum activation and effector functions in lung, spleen, peritoneum, bone marrow and blood. 98 In another study, Victorino et al 99 showed that NK cells resident in kidney directly mediated ischaemic kidney injury, which is common during septic shock and an indicator of poor prognosis. It is therefore noteworthy to perform more studies to examine how tissueresident NK cells could modulate compartment-specific inflammation and the multiple organ dysfunctions in lethal sepsis.…”
Section: Detrimental Role Of Nk Cells During Experimental Sepsismentioning
confidence: 99%
“…33,34,35 As natural killer (NK) cells comprise a large portion of the immunotolerant organs such as the lung and liver, we hypothesized that radiation to these sites may cause unique changes in specific NK cell populations. 33,36 We hypothesized that the systemic immune response to SAR would differ based on irradiated site, and set out to gain a comprehensive understanding of these differences to refine future clinical trials combining radiotherapy and immunotherapy. We prospectively collected blood samples prior to SAR and 1–2 weeks post-SAR from patients undergoing SAR to lung, liver, bone, or brain to measure changes in markers of the systemic immune response, such as cytokine/chemokine signatures and immunophenotype changes in peripheral blood mononucleated cells (PBMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Mice exhibited transient weight loss, clinical signs of inflammation, and limited mortality. Using this model, we had previously shown that NK cells are systemically activated over a 48 h acute period (Rasid et al, 2016). In the present study, we focused on the impact of endotoxemia on NK cells 14 days after LPS injection.…”
Section: Nk Cells Are Responsive After Endotoxemia and Acquire Memorymentioning
confidence: 97%